Methods of Sustainable Regulation of Agricultural Enterprises at the Present Stage - AIMURZINA, Baglan; KAMENOVA, Mazken; OMAROVA, Ainura; BAKYTGUL, Ainakanova; AIGUL, Kazkenova; NURGUL, Shaikenova (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018, 2019)
This article notes that one of the real sectors of the economy contributing to the development of Kazakhstan is agriculture. In this regard one of the priorities of the economy of the Republic of Kazakhstan is the accelerated sustainable development of agriculture on the basis of tax methods of regulation of agricultural producers. Taxes are one of the most important economic regulators, the basis of financial and credit mechanism of state regulation of economic sectors including agriculture. It is obvious that the success of economic reform in Kazakhstan depends to a large extent on the directions in which the transformation of the tax system of the country will go, how much the tax policy of the state will meet the requirements of the development of socially important sectors of the economy. The analysis of the structure of tax revenues from the subjects of sustainable development of agriculture of the Republic of Kazakhstan shows the impact of reducing the tax burden on the income of agricultural producers. Proposals for further improvement of tax regulation are given.